Drugs That Increase the Tone of the Human Body and Pharmacological Characteristics of Immunodeficiency Agents - Sokhib Rashidov Zamon oʻgʻli; Nilufar Ergasheva Agʼzamjon qizi; Elyor Zokirboyev Anvarjon o‘gli; Umidjon Akramov Abdusamad o‘g‘li; Aziza Egamberdieva Farkhod qizi (American Journal of Biomedicine and Pharmacy, 2025)
These days, psychoactive substances—such as cognitive enhancers, which can improve or restore brain function—as well as "recreational" drugs, like novel psychoactive substances (NPS), are still, and in some cases, are becoming, more widely available. There are advantages and disadvantages to using psychoactive drugs. While new medications to treat cognitive symptoms in neuropsychiatric or neurodegenerative disorders may be very helpful for many patient groups, the ease with which recreational NPS is becoming more widely available and the growing prevalence of cognitive enhancers among healthy individuals means that managing psychoactive substances effectively will become more and more important. A class of medications known as immunosuppressants works by preventing or lessening the body's immune response. The majority of these drugs work by making the body less likely to reject an organ transplant. Immunosuppressive drugs are required in solid organ transplantation in order to maintain organ rejection, manage late-stage immunosuppression, or initiate early-stage immunosuppression. This advancement is mostly due to the development of new drugs and advancements in post-transplant immunosuppressive protocols. These medications do, however, also raise the risk of infection, cancer, and certain negative side effects that are unique to each agent in patients, especially in pregnant women and those who are having fertility problems. The coronavirus disease, a contentious issue, has improved the effectiveness of immunosuppressive medications but still need further research. Many immunosuppressive protocols are used at transplant facilities worldwide; nevertheless, each patient may need a customized immunosuppression regimen to balance the benefits and potential risks of treatment, thereby removing the chance of recurrence of their initial disease.